CeO2 as a photocatalytic material for CO2 conversion: A review. (1st July 2022) - Tran, Duyen P.H.; Pham, Minh-Thuan; Bui, Xuan-Thanh; Wang, Ya-Fen; You, Sheng-Jie
Graphical abstract: Highlights: CeO2 photocatalyst properties are presented to suit for CO2 conversion into hydrocarbon fuels. The modification strategies of CeO2 are highlighted to improve CO2 conversion efficiency. Factors affecting the CO2 photo-conversion performance is thoroughly discussed. Future directions on the development of CeO2 in the realm of CO2 conversion are proposed. Abstract: Converting CO2 into add-value products is an appealing strategy to alleviate the environmental deterioration due to the high emission of atmospheric CO2 and energy shortage. Photocatalysis is a solar fuel production technology due to its potential to minimize carbon dioxide emissions while producing valuable compounds. Recently, the Cerium oxide (CeO2 )-based photocatalyst has drawn attention due to its outstanding characteristics: distinctive structure, simple oxidizing capabilities, non-toxicity, and environmental friendliness. However, the wide energy bandgap has restricted its applicability in photocatalytic CO2 conversion using solar energy. This review provided the various modification strategies, including metal and nonmetal doping, heterostructures, and oxygen vacancy creation, to improve the performance of pristine CeO2 . Besides, this review also explained the fundamental principles of CeO2 photocatalyst towards converting CO2 into valuable products. In addition, CeO2 -based photocatalytic composites are also proposed and discussed in term of performance and the effect of heterostructure on photocatalytic CO2 conversion. Finally, the challenges and prospects of the CeO2 in the photocatalytic CO2 conversion have been emphasized.